FATIGU TEST AND PARAMETRIC STUDY OF CRACKED STEEL PLATES REPAIRED BY CFRP - WU XiZhi; CHENG JunSheng; YANG Yu; HUANG Yi (Jixie qiangdu)
At the thin steel plates running a period,cracks may occur at the material or weld,and traditional repair methods aren’t suitable for cracks repair of the thin steel plates.But the method of drilling hole at the crack tip and pasting CFRP on the steel plates is a choice for crack repair.Firstly,through five groups of fatigue test,it analyzed the effect of the crack fatigue life of the hole joint CFRP reinforcement and the other methods.Then,based on the cohesive force theory,it established the finite element model of notch steel plate reinforced with CFRP.With the finite element model,it studied the repair parameters of the stiffness,length and width of CFRP.The results demonstrate that the remaining fatigue life of the hole joint CFRP reinforcement is better than drilling holes or pasting CFRP,and even more than the steel plate with no crack.So it is especially suitable for the thin-wall steel plate with short cracks.